2008
DOI: 10.1177/016173460803000409
|View full text |Cite
|
Sign up to set email alerts
|

Contrast Harmonic Detection with Chirp Excitation in 3f0 Transmit Phasing

Abstract: The method of third harmonic (3f0 transmit phasing is capable of providing effective tissue background suppression for contrast-to-tissue ratio (CTR) improvement in harmonic imaging. With the additional 3f0 transmit signal to generate both the frequency-sum and the frequency-difference components of harmonic signal, the tissue suppression is achieved when the two components are opposite in phase and mutually cancel out. One major problem in 3f0 transmit phasing is the limited signal-to-noise ratio (SNR) due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Therefore, this technique can be used in contrast imaging as well as in tissue-harmonic imaging. 21,22 These authors also suggested using the harmonic leakage signal to generate the second-harmonic reduction signal. 23,24 Multipulse Techniques However, in conventional harmonic imaging, the following problem is always encountered: if a short pulse, that is a broadband pulse, is transmitted, there is an inevitable spectral overlap between the fundamental and harmonic frequencies of the backscattered signals.…”
Section: Single-pulse Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, this technique can be used in contrast imaging as well as in tissue-harmonic imaging. 21,22 These authors also suggested using the harmonic leakage signal to generate the second-harmonic reduction signal. 23,24 Multipulse Techniques However, in conventional harmonic imaging, the following problem is always encountered: if a short pulse, that is a broadband pulse, is transmitted, there is an inevitable spectral overlap between the fundamental and harmonic frequencies of the backscattered signals.…”
Section: Single-pulse Techniquesmentioning
confidence: 99%
“…Therefore, this technique can be used in contrast imaging as well as in tissue-harmonic imaging. 21,22 These authors also suggested using the harmonic leakage signal to generate the second-harmonic reduction signal. 23,24…”
Section: Introductionmentioning
confidence: 99%
“…24 They reported improvements in the SNR, at the expense of a reduced agent-to-tissue contrast. It was also demonstrated that chirp-coded excitation improved the SNR of 3f 0 transmit phasing techniques; 25 however, the agent-to-tissue contrast was reduced. In another study, the contrast agent response to increasing and decreasing chirp-coded pulses was observed optically and acoustically.…”
Section: Introductionmentioning
confidence: 99%
“…Chirp-coded excitation is one such technique that has been widely investigated for contrast-enhanced ultrasound imaging. 14,[18][19][20][21][22][23][24][25][26][27] In a theoretical study, Barlow and colleagues reported an analytical solution to the Keller-Herring model, to predict the response of microbubbles to chirp-coded excitation. 18 A classical perturbative analysis was employed 28 to gain insight into the impact of excitation parameters on the nonlinear response.…”
Section: Introductionmentioning
confidence: 99%
“…The differences between these techniques lie in how the source pre-biasing signal is designed. shen et al proposed a technique transmitting a fundamental and a phase-shifted third-harmonic wave simultaneously to cancel the second harmonic [12], [13]. The same group also used the harmonic leakage signal to produce the secondharmonic reduction signal [14], [15].…”
Section: Introductionmentioning
confidence: 99%